PENERAPAN PROGRAM BIMBINGAN KONSELING UNTUK MENINGKATKAN MINDFUL SELF CARE PADA KESEJATRAAN PESERTA DIDIK DI SEKOLAH MENENGAH ATAS - Suprianto Baen; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The purpose of this study was to find out the application of the guidance and counseling program to improve mindful self-care in the welfare of students in senior high schools.The method used is quantitative research by analyzing and comparing the scale of self-care and adaptation of students with self-care awareness by using instruments to find out about this, as well as the library research method, namely analyzing previous research by proving that the development of counseling guidance programs is to increase mindfulness self-care in high school students is known by the results obtained by measuring using diagrams and table scales. The design used in this study was a survey research design, high school level student population, a sample of 32 people, questionnaire data collection instruments and a multilevel scale, descriptive data analysis techniques. The results of research from the field can be said that the positive behavior of students greatly influences their physical and spiritual health. For the entire population, the mean frequency is 3.44. A summary of the total average for each subscale is displayed graphically, namely to understand the extent to which participants are involved in activities and see which activities they like. Students vary in their feelings about the effectiveness of their personal self-care practices, and they actively seek ways to enhance these skills. Students also want to improve their self-care practices because they feel self-care plays an important role in OT. To help students achieve these goals, PL programs can support students' knowledge and self-care practices in a number of ways. Supporting students in developing health-promoting self-care practices can enhance their well-being and enhance their professional practice, ultimately improving the lives of the clients they serve.